Interactive dynamic scalp acupuncture enhances brain functional connectivity in bilateral basal ganglia ischemic stroke patients: a randomized controlled trial - Zhang, Chunxia; Pang, Tao; Chen, Yuan; Lai, Penghui; Nie, Rongrong; Wang, Yulong; Zhang, Shaohua (Frontiers in Neurology, 2025)
AimThis randomized controlled trial investigated the effects of interactive dynamic scalp acupuncture (IDSA) on brain functional connectivity density (FCD) in patients with bilateral basal ganglia ischemic stroke (BBGIS), focusing on its potential to enhance motor recovery.MethodsSeventy BBGIS patients (aged 45–75 years, 1–3 months post-stroke, Brunnstrom stage II–V) and 40 age-and sex-matched healthy controls (HCs) were enrolled. Resting-state functional MRI (rs-fMRI) assessed baseline FCD differences between groups, with regions showing significant alterations correlated to Fugl-Meyer Assessment (FMA) scores selected as seed points. Patients were randomized to IDSA (n = 35) or Sham IDSA (n = 35) therapy for 4 weeks. IDSA targeted the MS6 acupoint using stainless steel needles (0.3 × 40 mm) rotated at 200 rpm during active limb movement, while Sham IDSA used blunt needles without skin penetration. Post-treatment rs-fMRI and FMA evaluations were conducted.ResultsCompared to HCs, BBGIS patients exhibited reduced FCD in the right supplementary motor area (SMA_R) and right cerebellum-8 (C8_R), which positively correlated with FMA scores (r = 0.82 and r = 0.86, respectively; p < 0.0001). Post-treatment, the IDSA group showed significant increases in FCD in SMA_R (Δ = 0.64 ± 0.22, p < 0.001) and C8_R (Δ = 0.77 ± 0.91, p < 0.05), along with higher FMA scores (53.23 ± 13.6 vs. Sham 44.35 ± 11.2, p < 0.05), indicating improved motor function.ConclusionIDSA therapy enhances functional connectivity in SMA_R and C8_R, which are associated with motor recovery in BBGIS patients. These findings support IDSA as a potential intervention for stroke rehabilitation (Study registration: China National Clinical Trial Registry, ChiCTR2200055463).